2015
DOI: 10.1021/acsami.5b04116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrates on the Photoelectrochemical Reduction of Water over Cathodically Electrodeposited p-Type Cu2O Thin Films

Abstract: In this study, we demonstrate development of p-Cu2O thin films through cathodic electrodeposition technique at constant current of 0.1 mA/cm(2) on Cu, Al, and indium tin oxide (ITO) substrates from basic CuSO4 solution containing Triton X-100 as the surfactant at 30-35 °C. The optical and morphological characterizations of the semiconductors have been carried out using UV-vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. The band gap energy of ∼2.1 eV is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…As a consequence, the reported values of quantum efficiency for the photocathodes based on the electrodeposited Cu 2 O films are usually significantly less than 100% (≈1% [24], ≈26% [28], ≈70% [20]) making relevant a looking for methods of charge recombination suppression. Our previous studies have demonstrated that properties of the electrodeposited Cu 2 O films can be improved by variation of electrolyte composition [35,36]. Nevertheless, origins of these effects are not completely understood and require further research.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the reported values of quantum efficiency for the photocathodes based on the electrodeposited Cu 2 O films are usually significantly less than 100% (≈1% [24], ≈26% [28], ≈70% [20]) making relevant a looking for methods of charge recombination suppression. Our previous studies have demonstrated that properties of the electrodeposited Cu 2 O films can be improved by variation of electrolyte composition [35,36]. Nevertheless, origins of these effects are not completely understood and require further research.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the recently reported investigations are focused on Cu 2 O. [25][26][27][28][29][30][31][32] Due to the chemical instability and poor electron transfer, its nano-composites with other oxides or metal catalysts have been attempted. [33][34][35] On the other hand, CuO is chemically more stable than Cu 2 O but there are only few studies on the PEC response of CuO have been reported so far.…”
mentioning
confidence: 99%
“…The prominent characteristic peak at 218 cm −1 was assigned to the second-order Raman-allowed mode (2Γ 12 − ) of Cu 2 O. 28 The peak at 148 cm −1 could be ascribed to Raman scattering from phonons of symmetry (Γ − 15 ), 29 whereas the relatively weak peaks at 308, 416, and 515 cm −1 matched well with the second-order overtone mode, fourphonon mode (3Γ 12 − + Γ 25 − ), and Raman-allowed mode, respectively. 25,28 A shoulder peak at 635 cm −1 was marked to the infrared-allowed mode.…”
Section: ■ Results and Discussionmentioning
confidence: 98%